![(a - b - c) ^{2} - (a - b - c) ^{2} - 4b ^{2} + 4c ^{2} (a - b - c) ^{2} - (a - b - c) ^{2} - 4b ^{2} + 4c ^{2}](https://tex.z-dn.net/?f=%28a+-+b+-+c%29+%5E%7B2%7D++-+%28a+-+b+-+c%29+%5E%7B2%7D++-+4b+%5E%7B2%7D++%2B+4c+%5E%7B2%7D++)
simplify and factorise
Answers
Answered by
0
Answer:
(a-b-c)²-(a-b-c)²-4b²+4c²
0-4b²+4c²
4c²-4b²
(2c)²-(2b)²
(2c+2b)(2c-2b)
2(c+b)(c-b)
anitavijaynirban1976:
Thx for marking brainliest
Answered by
0
a^2 - b^2 - c^2 - a^2 + b^2 + c^2 - 4b^2 + 4c^2
a^2 - a^2 = 0
b^2 - b^2 = 0
c^2 - c^2 = 0
- 4b^2 + 4c^2
4(c^2 - b^2)ans..
a^2 - a^2 = 0
b^2 - b^2 = 0
c^2 - c^2 = 0
- 4b^2 + 4c^2
4(c^2 - b^2)ans..
Similar questions